Pertanggung Jawaban Hukum Terhadap Pelaku Tindak Pidana Judi Online Di Indonesia - Sugeng Riyanto; Nur Handayani; Moh Taufik; Rendra Aranggraeni (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
This study examines the legal liability of perpetrators of onlinegambling crimes in Indonesia, in line with the rapid development ofinformation technology that has given rise to new forms of crime,including gambling via the internet. Online gambling has become a worrying phenomenon because it is easily accessible, addictive, and has a negative impact on the morals and social life of society. Thisstudy aims to identify the legal elements in online gambling crimesand analyze how law enforcement is carried out against perpetratorsof these crimes in Indonesia. This study uses a normative juridicalmethod with a statutory approach and case studies. The results of thestudy indicate that criminal liability for perpetrators of online gamblingcan be imposed based on Article 303 of the Criminal Code and Article27 paragraph (2) in conjunction with Article 45 paragraph (2) of theITE Law. However, there are still obstacles in the implementation ofthe law, especially related to effective supervision and action by lawenforcement officials. This study recommends strengtheningregulations and increasing the capacity of law enforcement officials indealing with cybercrime, including online gambling. It is hoped thatthe results of this study can contribute to the development of criminallaw, especially in the aspect of combating information technologybasedcrimes.